DESIGN OF AUTOMATED CONTROL SYSTEM EVACUATION IN AN EMERGENCY ON THE PRINCIPLE OF SYSTEMS ENGINEERING - S. S. Valeev; N. V. Kondratyeva; A. F. Agletdinova (Научный вестник МГТУ ГА)
One of the objectives of the management of infrastructure facilities is to ensure efficient evacuation in an emergency. The problem of the evacuation is related to the heterogeneity of data, its’ large volume, the loss of part of the information infrastructure under the influence of destructive factors. The concept design of the automated evacuation control system based on system engineering is considered. It involves the use of a systematic approach, modern information technologies, as well as simulation. The actuality of the use of technology solutions for big data management tasks in real time is proved. As a tool for distributed processing, cluster prototype with low power consumption computers is proposed.